Implementation study of SARS-CoV-2 antigen lateral flow tests in men's professional (Premiership) rugby union sports squads in England during the COVID-19 pandemic. Issue 2 (February 2022) - Finch, Lorna S; Harris, Adrian; Lester, Catherine; Veal, Dawn; Jones, Karen; Fulton, Jamie; Jones, Lewis; Lee, Matt; Walker, Tony; Rossiter, Mike; Cross, Matt; Kemp, Simon; et al.
Highlights: To date this is the first ever service evaluation of SARS-CoV-2 Ag-RDTs in elite professional rugby teams. Despite the high acceptability of Ag-RDTs amongst players and staff in this the study, the performance needs ongoing real-world evaluation to support rapid transition to self-swabbing. This study highlights the need for continued service evaluations for SARS-CoV-2 Ag-RDTs in elite sport settings. Abstract: This study evaluated the validity and utility of antigen-detection rapid diagnostic tests (Ag-RDTs) for SARS-CoV-2 in elite sports. The data on utility, ease of use and application for Ag-RDTs as a new testing format were positive from players and staff. This evaluation was limited by the low prevalence of SARS-CoV-2 circulating within the three squads. This study highlights the need for continued service evaluations for SARS-CoV-2 Ag-RDTs in elite sport settings.